2011
DOI: 10.1007/s00261-011-9719-8
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial invasion by endometrial carcinoma: evaluation with 3.0T MR imaging

Abstract: In evaluation of the depth of myometrial invasion by endometrial carcinoma, 3.0T MR imaging has a high diagnostic accuracy that is equivalent to that of previously reported 1.5T MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…With advancements in MRI technology, diffusion-weighted imaging (DWI-MRI) applied in gynaecological diseases also has been reported in several studies with promising results [7-9]. Compared with 1.5 T, the signal-to-noise ratio at 3 T has been increased and background suppression has been improved, which allows better categorization of variable components of ovarian diseases [10,11]. Studies with focus on primary adnexal lesions evaluated by 3.0 T (3 T) still are limited to date.…”
Section: Introductionmentioning
confidence: 99%
“…With advancements in MRI technology, diffusion-weighted imaging (DWI-MRI) applied in gynaecological diseases also has been reported in several studies with promising results [7-9]. Compared with 1.5 T, the signal-to-noise ratio at 3 T has been increased and background suppression has been improved, which allows better categorization of variable components of ovarian diseases [10,11]. Studies with focus on primary adnexal lesions evaluated by 3.0 T (3 T) still are limited to date.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with deep invasion of the myometrium, dynamic contrast-enhanced MRI significantly improves the signal-to-noise ratio for tumour and uterine wall muscle, allowing more accurate determination of the depth of myometrial invasion. 4,16,17 T2WI-and T 1 weighted imagingenhanced scanning have demonstrated accuracies of 73-86% and 78-88%, respectively, for assessing depth of muscle invasion, and this accuracy can be further increased to 82-92% for enhanced dynamic scanning. 9,[16][17][18] The results of the current study showed that dynamic enhanced FLASH-3D imaging technology increased the accuracy of pre-operative evaluation of depth of myometrial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,17 T2WI-and T 1 weighted imagingenhanced scanning have demonstrated accuracies of 73-86% and 78-88%, respectively, for assessing depth of muscle invasion, and this accuracy can be further increased to 82-92% for enhanced dynamic scanning. 9,[16][17][18] The results of the current study showed that dynamic enhanced FLASH-3D imaging technology increased the accuracy of pre-operative evaluation of depth of myometrial invasion. The study by Emlik 4 has demonstrated that in differentiation of deep myometrial invasion from superficial myometrial invasion, the sensitivity, specificity, accuracy, PPV and NPV were 100%, 85%, 89%, 68.4%, and 100% on dynamic 3D FLASH volume interpolated gradient echo MR images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations